2009
DOI: 10.1158/0008-5472.can-09-1289
|View full text |Cite
|
Sign up to set email alerts
|

mTOR Signal and Hypoxia-Inducible Factor-1α Regulate CD133 Expression in Cancer Cells

Abstract: The underlying mechanism regulating the expression of the cancer stem cell/tumor-initiating cell marker CD133/prominin-1 in cancer cells remains largely unclear, although knowledge of this mechanism would likely provide important biological information regarding cancer stem cells. Here, we found that the inhibition of mTOR signaling up-regulated CD133 expression at both the mRNA and protein levels in a CD133-overexpressing cancer cell line. This effect was canceled by a rapamycin-competitor, tacrolimus, and wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
111
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 134 publications
(123 citation statements)
references
References 17 publications
10
111
2
Order By: Relevance
“…Real-time reverse-transcription PCR (RT-PCR) was performed as described. 11 In brief, complementary DNA was prepared from the total RNA obtained from each surgical frozen section using a GeneAmp RNA-PCR kit (Applied Biosystems). Real-time RT-PCR amplification was performed using a Thermal Cycler Dice (TaKaRa, Otsu, Japan) in accordance with the manufacturer's instructions under the following conditions: 95 C for 5 minutes, followed by 50 cycles of 95 C for 10 seconds and 60 C for 30 seconds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Real-time reverse-transcription PCR (RT-PCR) was performed as described. 11 In brief, complementary DNA was prepared from the total RNA obtained from each surgical frozen section using a GeneAmp RNA-PCR kit (Applied Biosystems). Real-time RT-PCR amplification was performed using a Thermal Cycler Dice (TaKaRa, Otsu, Japan) in accordance with the manufacturer's instructions under the following conditions: 95 C for 5 minutes, followed by 50 cycles of 95 C for 10 seconds and 60 C for 30 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was performed as described. 11 The following antibodies were used: monoclonal FGF3 (R&D Systems, Minneapolis, MN), FGF4 and FGFR2 antibodies (Santa Cruz Biotechnology, Santa Cruz, CA), and phosphorylated FGFR and horseradish peroxidase-conjugated secondary antibodies (Cell Signaling Technology, Beverly, MA). NIH-3T3 cells were exposed to the indicated concentrations of sorafenib for 2 hours and were then stimulated with FGF4-conditioned medium for 20 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…The methods used in this section have been previously described (12). GAPD was used to normalize the expression levels in the subsequent quantitative analyses.…”
Section: Methodsmentioning
confidence: 99%
“…We found 94 genes differentially regulated by HIF-1α in both settings (Chapter 5). Many of these genes, including Vegf, Egln3 (PHD3), Aldoc and Pdk1 were known HIF-1α target genes and are involved in cancer cell migration and invasion, tumor initiation and growth, and metastasis [61,154] [ 72,116]. One of the genes we found to be the most differentially up-regulated in WT cells and tumors is the enzyme creatine kinase brain isoform (Ckb).…”
Section: Chapter 6 Creatine Kinase B (Ckb) Activity Is Hif-1-dependementioning
confidence: 91%
“…Interestingly, in gliomas, the TIC population was enriched via cell sorting based on the expression of a single cell surface marker, CD133 (PROM1). PROM1, a transmembrane protein without a known ligand, is a known hypoxia-responsive protein regulated by HIF-1 [116,117]. Several studies have shown that the population of breast tumor cells with the ability to self-renew is enriched with the ability to initiate tumorigenesis in vivo [118][119][120][121].…”
Section: Hypoxia and Cancer Stem Cells Cancer Stem Cell Theory And Rementioning
confidence: 99%